Lactiplantibacillus plantarum IS-10506 Enhances Tight Junction Integrity in Bronchial Epithelium: An Experimental Study - Fetarayani, Deasy; Soegiarto, Gatot; Surono, Ingrid Suryanti; Endaryanto, Anang; Athiyyah, Alpha Fardah; Hernaningsih, Yetti; Fauziah, Dyah; Sudiana, I Ketut; Utomo, Budi; Prakoeswa, Cita Rosita Sigit (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Airway epithelium constitutes the initial structural defense against inhaled allergens, with its integrity primarily maintained through the formation of tight junctions (TJ) consisting of claudins, occludins, and zonula occludens (ZO). Currently, the effects of probiotics on airway TJ remain unclear. Therefore, this study was conducted to explore the impact of Lactiplantibacillus plantarum IS-10506, a native probiotic from Indonesia, on bronchial epithelial TJ in a mouse model of allergic airway inflammation.METHODS: Twenty-four BALB/c mice were randomly assigned to three groups: negative control, positive control subjected to Dermatophagoides pteryonissinus (Der p) sensitization and challenge, and treatment group exposed to Der p and administered L. plantarum IS-10506 since one week before sensitization up to three weeks after. The expression levels of claudin-18, occludin, and ZO-1 were investigated through immunohistochemistry analysis and quantified based on the immunoreactive score (IRS). RESULTS: The results of this study demonstrated that L. plantarum IS-10506 significantly enhanced the expressions of claudin-18, occludin, and ZO-1 (p<0.05).CONCLUSION: These findings underscore the probiotic's role in fortifying the integrity of airway TJ.KEYWORDS: allergic inflammation, probiotic Lactiplantibacillus plantarum, immunology, respiratory system, tight junction, occludin, claudin, zonula occludens